Noninvasive detection of hepatic steatosis in patients without ultrasonographic evidence of fatty liver using the controlled attenuation parameter evaluated with transient elastography - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
ObjectiveAlthough ultrasound is a useful technique for detecting hepatic steatosis, it cannot provide a precise determination of hepatic fat content. A novel attenuation parameter named controlled attenuation parameter (CAP) has been developed to process the raw ultrasonic signals acquired by Fibroscan. The aim of this study was to determine the percentage of hepatic steatosis in apparently healthy Turkish individuals using the proposed diagnostic cut-off points for CAP. In addition, we sought to investigate the association of CAP with the traditional risk factors for nonalcoholic fatty liver disease in a screening setting.Materials and methodsIn the present study, 102 Turkish individuals without evidence of fatty liver on ultrasound and normal aminotransferase levels underwent CAP measurements by means of Fibroscan.ResultsThe mean (SD), median (minimum-maximum), and 5th and 95th percentile values of CAP values in this cohort of 102 individuals were 206.99 (48.12), 210.5 (100.0-314.0), 113.4 and 280.2 dB/m, respectively. Using the cut-offs of 222, 238, and 283 dB/m for CAP, there were 39 (38.2%), 23 (22.5%), and five (4.9%) individuals out of 102 who had at least 10% steatosis despite normal liver findings on ultrasound. After allowance for potential confounders, CAP was independently associated with BMI (=0.39, t=3.5, P<0.001) and the number of metabolic syndrome criteria (=0.24, t=2.1, P<0.05).ConclusionThese results hold promise for early noninvasive detection of hepatic steatosis on the basis of CAP assessment. (C) 2013 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: controlled attenuation parameter; Fibroscan; hepatic steatosis; nonalcoholic fatty liver disease; NONALCOHOLIC STEATOHEPATITIS; IMAGING TECHNIQUES; DISEASE; BIOPSY; CAP; DIAGNOSIS; FIBROSCAN(R); FIBROTEST; FIBROSIS; PITFALLS